Relationships for vitamin D with childhood height growth velocity and low bone mineral density risk - Xiao, Pei; Cheng, Hong; Wang, Liange; Hou, Dongqing; Li, Haibo; Zhao, Xiaoyuan; Xie, Xianghui; Mi, Jie (Frontiers in Nutrition, 2023)
Objective: To investigate how serum 25-hydroxyvitamin D (25[OH]D) affects height growth velocity and the risk of low bone mineral density (BMD) in children. Design: A population-based prospective cohort study. Patients and Methods: A total of 10 450 participants with complete follow-up records from a cohort were included in the current study. Serum 25(OH)D concentrations were measured at baseline and 2-year follow-up, and the average of 2-time measurements was used for analysis. Low BMD was defined as calcaneus speed of sound Z-score ≤ -1. The associations of vitamin D with height growth velocity and the risks of incident low BMD were evaluated using adjusted β and risk ratio (RR). Results: After multivariable adjustment, an inverse L-shaped association between serum 25(OH)D concentrations and height growth velocity was observed, leveling off up to 40-60 nmol/L. Overall, each 10 nmol/L higher serum 25(OH)D concentration was associated with a 0.14 cm/year higher height growth velocity (P <0.001) and a 6% decreased risk of low BMD (RR [95%CI]: 0.94 [0.88 0.99]). Compared to those with vitamin D deficiency, participants who had sufficient vitamin D had a 21% lower risk for low BMD (RR[95%CI]: 0.79 [0.63 0.99]). However, no significant associations between vitamin D and the risk of low BMD were found in overweight and obese children. Conclusion: These findings highlight the importance of maintenance of sufficient 25(OH)D concentrations and healthy body weight during childhood in height growth and bone health promotion.